(untitled) (Malay Literature, 2022)
The Malay Hikayat Seri Rama (HSR) represents a Hindu legend that was heavily Islamicized in its final Malay form (as presented to Oxford University in 1633). This paper seeks to discern the ethical values of HSR. These values are included in sentences spoken by the narrator, and in sentences spoken by the characters themselves. The values are described in single words (just, brave, generous, etc.), phrases, and occasionally whole paragraphs. The values are related to the administration of the state and to the maintenance of an army. They are particularly male values. It is suggested that the source of these values lies in the Arabic-Persian wisdom tradition, as particularly represented in Malay by Taj al Salatin, a work from the same time and place as HSR (Aceh, North Sumatera, in the early 17th century). A brief glance of several Indian business websites related to the contemporary relevance of Valmiki’s Ramayana reveals a series of manipulative selfish propositions. The paper concludes by emphasizing on the contemporary importance of individual responsibility, such as justice, fairness, awareness, thoroughness, compassion, and maintaining “a good name”. Full text: PDF